Energy Consumption Analysis of WirelessHART Adaptor for Industrial Wireless Sensor Actuator Network - Chung, T.D. (Elsevier B.V., 2017)
The fast development of the emerging industrial wireless protocols and technologies such as WirelessHART has enabled their use in industrial sensing application. Their control application is still limited to mainly research environment. Apart from stringent requirement of reliability, energy consumption (or battery's life-time) of field device is also a decisive concern for control in wireless sensor actuator network (WSAN). The key challenge for the battery is to have an operational life between four to ten years. However, recent works have not addressed this necessity from electronic design and control perspectives. Therefore, this paper presents an analysis of a designed WirelessHART adaptor emphasizing on the battery's life-time requirement. © 2017 The Authors.